An assessment of some closed-form expressions for the Voigt function. (June 2016) - Schreier, Franz
Abstract: Using triangular function approximations of the Gaussian, closed-form analytical representations of the Voigt function K ( x, y ) in terms of elementary functions can be derived. The performance of the approximations is studied by comparison with more exact numerical algorithms for the closely related complex error function, indicating serious problems for small y . Abstract : Highlights: Closed-form analytical approximation of Voigt function in terms of arctangens and logarithms. Good for large y, but substantial accuracy problems for small y . Moderate computational efficiency.